A randomized, controlled pilot study of warm handoff versus fax referral for hospital-initiated smoking cessation among people living with HIV/AIDS. (March 2018) - Mussulman, Laura M.; Faseru, Babalola; Fitzgerald, Sharon; Nazir, Niaman; Patel, Vivek; Richter, Kimber P.
Abstract: Introduction: The prevalence of smoking among people living with HIV/AIDS (PLWHA) remains higher than the general population. Life expectancy among PLWHA has increased over the past decade, however, PLWHA who smoke will die younger than their non-smoking peers. The primary aim of this pilot study was to examine the effects of warm handoff versus fax referral to the quitline for smoking cessation among hospitalized smokers living with HIV/AIDS. Methods: 25 smokers with a diagnosis of HIV/AIDS hospitalized at a Midwestern academic medical center in 2012–2013 (19 male; mean age = 47.7; 48% African-American) were identified, approached, and randomized to one of two treatment arms. At the bedside for patients in warm handoff, staff telephoned the quitline for on-the-spot enrollment and counseling. Participants randomized to fax were fax-referred to the quitline on the day of discharge. The quitline provided continued outpatient counseling to participants in both conditions. The main outcome was verified tobacco abstinence at 6-months post randomization. Results: Enrollment and participation in quitline counseling was high among both warm handoff (100%) and fax-referred (71.4%) PLWHA participants. Nearly all completed follow up for outcome data collection at 6 months. Verified abstinent rates were 45.5% in warm handoff versus 14.3% in fax referral at 6 months (not significant). Conclusions: Hospitalized smokers living with HIV/AIDS were highly engaged in quitline services. Warm handoff seems a promising intervention for hospitalized PLWHA that requires further exploration. Clinical Trials RegistrationNCT01305928 . Highlights: Tobacco use disorder continues to lower the lifespan and decrease the quality of life among PLWHA. Hospitalization is an excellent time to initiate tobacco treatment among PLWHA who are interested in quitting tobacco. A warm handoff to tobacco quitlines during hospitalization is an extremely promising approach for helping PLWHA quit smoking.